Pemenuhan Legalitas Usaha untuk Meningkatkan Kualitas dan Daya Saing UMKM dalam Pengolahan Hasil Bumi di Desa Warunggunung Kecamatan Warunggung Kabupaten Lebak - Jumhana, Enjum; Jefri, Ulfi; Basrowi; Mulyawan, galuh; Hasan, Siddiq (Abdimas Siliwangi, 2024)
This service discusses the importance of business legality in improving the quality and competitiveness of MSMEs in Warunggunung Village, Warunggunung Subdistrict, Lebak Regency. Business legality, such as the Business Identification Number (NIB), Home Industry Food Production Certificate (PIRT), and Halal Certification, are crucial aspects that are often overlooked by micro, small and medium enterprises (MSMEs), which can limit market access and reduce consumer trust. This mentoring program aims to assist MSMEs in the village in obtaining business legality through socialization, training, and intensive mentoring. The program involves collaboration between universities, local governments, and related institutions. The results of the program show a significant increase in MSMEs' understanding of the importance of business legality, with an increase from 40% to 93% after the program was implemented. In conclusion, this program successfully raised awareness and fulfillment of business legality among MSMEs, which in turn contributes to the improvement of their product competitiveness and quality in the market.Keywords: Legality, MSMEs, Competitiveness